Functional current collector and battery comprising same

By using coated modified fillers in the polyester composite film of lithium-ion batteries, the problem of instability of the polyester substrate in the electrolyte is solved, significantly improving the anti-swelling and thermal stability of the battery, thereby improving the electrochemical and safety performance of the battery.

CN119725555AActive Publication Date: 2025-03-28JIANGYIN NANOPORE INNOVATIVE MATERIALS TECH LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411896326.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-28
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

In existing lithium-ion batteries, the polyester substrate is unstable in strong acidic and alkaline electrolytes, which are prone to dissolve, swell or react, resulting in aging of chemical bonds between the metal layer and the polyester film, reducing the cycling capacity and safety performance of the battery.

Method used

By coating the filler (inorganic material or polymer) with a first silane coupling agent, a polyester composite film is formed, which improves the dispersion and connection tightness of the filler in the polyester, and enhances the anti-swelling performance and thermal stability of the polyester film.

Benefits of technology

It effectively improves the anti-swelling performance and thermal stability of the polyester composite film, extends the cycle life of the battery, and improves the electrochemical performance and safety performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005201968300000101
    Figure BDA0005201968300000101
  • Figure BDA0005201968300000111
    Figure BDA0005201968300000111
Patent Text Reader

Abstract

The invention provides a functional current collector and a battery comprising the same, the functional current collector comprises a base film, and the base film is a polyester composite film; the polyester composite film comprises polyester and a filler, and the filler is coated with a first silane coupling agent; the filler is an inorganic material or a polymer; the structural general formula of the first silane coupling agent is (R1O) 3-Si-R2-R3. The functional current collector can effectively relieve the swelling and dissolving phenomenon of the polyester film on the substrate layer and effectively improve the anti-swelling performance of the polyester film, so that the electrochemical performance and the safety performance of the battery prepared from the functional current collector are effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a functional current collector and a battery comprising the same. Background Art

[0002] The vigorous development of metal plating technology on the surface of plastic layers has provided a new way out for new current collectors for large-scale application of lithium-ion batteries. By using an electronically insulating polymer plastic layer as a substrate and depositing a thin layer of metal on its surface, a new sandwich structure metallized polymer functional current collector (MPCC, metal layer + polymer layer + metal layer) can be prepared. MPCC has the dual advantages of polymer plastics and metals, such as light weight, high mechanical strength and elongation, solvent resistance, corrosion resistance, wear resistance, light resistance, conductivity, thermal shrinkage, etc., thereby achieving good cycle stability, reducing the thickness of the current collector, and improving energy density and safety.

[0003] The polymer substrate plays an indispensable role in MPCC. It has the characteristics of insulation, thermal shrinkage, melting, and ductility difference between the polymer and the metal layer deposited on the surface, which can significantly improve the safety of batteries using MPCC under mechanical abuse such as needle puncture and extrusion. Among these polymer materials, polyester film has significant advantages such as high tensile strength, excellent thermal stability, good durability, self-extinguishing and strong flame retardancy. In addition, polyesters such as PET have good mechanical properties even at temperatures as low as -60°C. Polyester has become a widely used substrate material in MPCC applications because of its excellent physical and chemical properties, advanced technology and large-scale production make it low in cost, good in heat resistance, and can be evaporated.

[0004] However, since polyester contains a large number of ester bonds, it is not stable in strong acidic and alkaline electrolytes and is easily dissolved, swelled or reacted to depolymerize the polyester. If polyester depolymerizes and dissolves into the electrolyte, it will increase the viscosity of the electrolyte, slow down the ion transmission rate, and increase the internal resistance of the lithium-ion battery. As the cycle time increases, the swelling and dissolution reaction of polyester causes the chemical bonds between the metal layer and the polyester film to gradually age during long-term use, and the interfacial adhesion and peel strength between the metal layer and the substrate gradually weaken, resulting in a decrease in cycle capacity.

[0005] In the prior art, nucleating agents such as SiO2 are often added to the functional current collector. When immersed in the electrolyte for a long time, the nucleating agents will be dissolved and precipitated, which will easily cause the swelling and dissolution of the polyester film. The above phenomenon is particularly obvious after high-temperature cycles. The damage to the polyester film in the functional current collector will also accelerate the damage to the conductive layer, which will not only cause the loss of battery capacity, but also cause great safety hazards, which will have a great impact on the electrochemical performance and safety performance of the battery electrode made of this functional current collector. Summary of the invention

[0006] In order to solve the problems and shortcomings in the prior art, the present invention provides a functional current collector and a battery comprising the same. The functional current collector can effectively alleviate the swelling and dissolution phenomenon of the base layer polyester film, effectively improve the anti-swelling performance of the polyester film, and thus effectively improve the electrochemical performance and safety performance of the battery prepared by the functional current collector.

[0007] According to the first aspect of the present invention, a functional current collector is provided, comprising a base film, the base film being a polyester composite film; the polyester composite film comprising polyester and a filler, the filler being coated with a first silane coupling agent; the filler being an inorganic material or a polymer; the general structural formula of the first silane coupling agent being (R1O)3-Si-R2-R3; wherein R1 comprises: a substituted or unsubstituted C1 to C4 alkyl group; R2 comprises one of the following: a substituted or unsubstituted C1 to C18 straight-chain alkyl group, a substituted or unsubstituted C1 to C18 branched alkyl group, a substituted or unsubstituted C2 to C18 straight-chain alkenyl group having at least one double bond, a substituted or unsubstituted C2 to C18 straight-chain alkenyl group having at least one double bond, at least one branched alkenyl group with double bond, a substituted or unsubstituted straight-chain alkynyl group with C2-C18 and at least one triple bond, a substituted or unsubstituted branched alkynyl group with C2-C18 and at least one triple bond, a substituted or unsubstituted saturated cycloalkyl group with C3-C18, a substituted or unsubstituted at least partially unsaturated cycloalkyl group with C3-C18, a substituted or unsubstituted saturated cycloalkyl group with C3-C18 and no -NH-, a substituted or unsubstituted saturated cycloalkyl group with C3-C18 and at least one -NH-; R3 includes one of the following: hydroxyl, amino, vinyl, mercapto, acrylate, epoxy, halogen, alkali metal group.

[0008] The present invention coats the filler with a silane coupling agent containing a specific chemical formula and an active group. The silane coupling agent has an active organic group and a silane group. The active organic group can react with the polymer. The silane group undergoes a self-polymerization reaction through hydrolysis and polycondensation, and can connect to an inorganic surface. Therefore, the silane coupling agent can be coated on the surface of the polymer or inorganic material, and effectively connected to the polyester, so that the filler and the polyester form a uniform inorganic-organic or organic-organic network. When the filler is an inorganic material, since the inorganic material particles have poor dispersibility in the organic polyester, the silane coupling agent can more significantly improve the dispersibility of the inorganic material particles in the polyester after surface coating and modification of the inorganic material, reduce the roughness of the polyester composite film, thereby improving the bonding force between the base film and the base layer, and optimizing the overall structural stability and mechanical properties of the functional current collector.

[0009] Therefore, the filler after the above-mentioned silane coupling agent coating modification can be dispersed particularly evenly in the polyester, and because the filler is coated and modified by the silane coupling agent, the connection tightness between the filler and the polyester is greatly improved, which can change the crystallization temperature and melting temperature of the polyester composite film, and at the same time, the anti-swelling performance of the polyester composite film formed can be further improved to avoid the dissolution of the polyester composite film. In addition, the silane coupling agent increases the contact area between the polyester polymer and the filler, and enhances the bonding force between molecules and molecules, which can effectively fix the filler and prevent the filler from overflowing into the electrolyte, that is, greatly reducing the precipitation of the filler, avoiding its threat to the safety performance and electrochemical performance of the battery. Finally, since the Si-O bond has a higher bond energy (363kJ / mol), it is relatively stable and also plays a fixing role on the filler, and the heat resistance and high temperature resistance are both very high, which significantly improves the thermal stability of the polyester composite film, and avoids thermal damage when subjected to high temperature and local heat energy, thereby improving the stability and high temperature cycle performance of the battery based on this functional current collector. In summary, introducing the filler coated with the silane coupling agent in the present invention into the preparation of the polyester composite film can greatly improve the thermal stability and anti-swelling and dissolution properties of the polyester composite film. Therefore, it can avoid the damage of the polyester composite film in the functional current collector due to swelling and dissolution, which leads to a decrease in the electrochemical performance and safety performance of the battery, thereby effectively improving the electrochemical performance and safety performance of the battery.

[0010] Preferably, R3 comprises one of the following: vinyl, amino, mercapto, epoxy, acrylate.

[0011] Preferably, the thickness of the polyester composite film is 1.0-10 μm. Considering the application requirements of the functional current collector and the difficulty and cost of the preparation process, the thickness of the polyester composite film within the above range can better meet various requirements.

[0012] Preferably, the inorganic material includes at least one of carbon black, graphite, graphene, aluminum, zinc, aluminum oxide, zinc oxide, iron oxide, silicon dioxide, titanium dioxide, montmorillonite, kaolin, calcium carbonate, and glass fiber; the polymer includes at least one of polyamide resin, epoxy resin, phenolic resin, polycarbonate resin, polyamide resin, and acrylonitrile-butadiene-styrene copolymer resin.

[0013] Preferably, the preparation of the polyester composite film comprises the following steps: S1. dispersing the filler in a first alcohol solvent, adding a first silane coupling agent thereto, wherein the molar ratio of the filler to the first silane coupling agent is 1:(0.1-0.5), heating to 75-85°C for reaction for 20-50 minutes, cooling, centrifuging to remove the solvent, and dispersing again in a second alcohol solvent to obtain a solution containing the first silane coupling agent-coated filler; S2. adding the second silane coupling agent and the solution containing the first silane coupling agent-coated filler obtained in S1 to a polyester masterbatch, heating to 75-85°C for reaction for 10-30 minutes, and subjecting the obtained mixture to melt-extrusion-biaxial stretching to obtain the polyester composite film; wherein the molar ratio of the polyester masterbatch: the first silane coupling agent-coated filler: the second silane coupling agent is 1:(0.1-0.25):(0.01-0.2).

[0014] In the polyester composite film prepared by the above steps, the filler can be fully and evenly dispersed in the polyester composite film, effectively improving the anti-swelling performance and thermal stability of the polyester composite film. In the polyester composite film prepared by the above steps, because the filler is very tightly connected to the polyester, it will not easily precipitate after immersion electrolysis. Therefore, the polyester composite film prepared by the preparation method has more excellent comprehensive performance, which can further improve the electrochemical performance and safety performance of the battery.

[0015] Preferably, in S1, the first alcohol solvent and the second alcohol solvent independently include at least one of methanol and ethanol.

[0016] Preferably, the general structural formula of the second silane coupling agent is (R1O)3-Si-R2-R3; wherein R1 includes: a substituted or unsubstituted C1-C4 alkyl group; R2 includes one of the following: a substituted or unsubstituted C1-C18 straight-chain alkyl group, a substituted or unsubstituted C1-C18 branched alkyl group, a substituted or unsubstituted C2-C18 straight-chain alkenyl group with at least one double bond, a substituted or unsubstituted C2-C18 branched alkenyl group with at least one double bond, a substituted or unsubstituted C2-C18 straight-chain alkenyl group with at least one double bond, The invention relates to a straight-chain alkynyl group having a triple bond, a substituted or unsubstituted C2-C18 branched alkynyl group having at least one triple bond, a substituted or unsubstituted C3-C18 saturated cycloalkyl group, a substituted or unsubstituted C3-C18 at least partially unsaturated cycloalkyl group, a substituted or unsubstituted C3-C18 saturated cycloalkyl group not containing -NH-, a substituted or unsubstituted C3-C18 saturated cycloalkyl group containing at least one -NH-; R3 includes one of the following: hydroxyl, amino, vinyl, mercapto, acrylate, epoxy, halogen, and alkali metal group.

[0017] Preferably, the first silane coupling agent and the second silane coupling agent are of the same type; or, the first silane coupling agent and the second silane coupling agent are of different types.

[0018] Preferably, in S1, the first alcohol solvent and the second alcohol solvent independently include at least one of methanol and ethanol.

[0019] Preferably, the functional current collector includes a first protective layer, a first metal layer, a first transition layer, a polyester composite film, a second transition layer, a second metal layer, and a second protective layer in sequence. The function of the transition layer is to enhance the bonding force between the polyester composite film and the metal layer, the function of the metal layer is to conduct electricity, and the function of the protective layer is to prevent the metal conductive layer from being chemically corroded or physically damaged. Furthermore, the functional current collector includes two transition layers, two metal layers, and two protective layers, which can further enhance the performance of the functional current collector in various aspects, so that the functional current collector has more excellent mechanical properties, electrical conductivity, and electrolyte resistance.

[0020] Preferably, the first transition layer and the second transition layer independently include at least one of aluminum oxide, silicon oxide, titanium oxide, nickel, chromium, titanium, nickel-chromium alloy, nickel-chromium-copper alloy, and silicon-aluminum alloy.

[0021] Preferably, the bonding force between the first transition layer and the second transition layer and the adjacent first metal layer and the second metal layer is 100-900 N / m. The bonding force between the transition layer and the metal layer (conductive layer) will affect the relative movement between the metal layer and the polyester film during the deformation of the functional current collector, thereby affecting the deformation and fission behavior of the metal layer, and further affecting its effect on improving the safety performance of the battery.

[0022] Preferably, the first metal layer and the second metal layer independently include at least one of aluminum, copper, gold, silver, nickel, zinc, or a metal alloy formed by a combination of at least two of the above metals.

[0023] Preferably, the first protective layer and the second protective layer independently include at least one of nickel, chromium, nickel-chromium alloy, nickel-based alloy, copper-based alloy, copper oxide, aluminum oxide, nickel oxide, chromium oxide, cobalt oxide, copper-chromium oxide, graphite, carbon black, carbon nano-quantum dots, carbon nanotubes, carbon nanofibers, graphene and graphene oxide.

[0024] Preferably, the thickness of the first transition layer and the second transition layer are independently 5-50 nm.

[0025] Preferably, the thickness of the first metal layer and the second metal layer is independently 400-2000 nm. If the metal layer is too thin, the conductivity is poor; if it is too thick, the functional current collector is too heavy, which is not conducive to improving the energy density of the battery.

[0026] Preferably, the thickness of the first metal layer and the second metal layer is independently 800-1200 nm. Metal layers with thickness within this range are more conducive to taking into account both conductivity and energy density of the battery.

[0027] Preferably, the preparation method of the first metal layer and the second metal layer includes one or more of evaporation, magnetron sputtering, chemical plating, electroplating, and CVD.

[0028] Preferably, the first metal layer and the second metal layer are prepared by electroplating or magnetron sputtering.

[0029] Preferably, the thickness of the first protective layer and the second protective layer are independently 10-100 nm.

[0030] Preferably, the thickness of the first protective layer and the second protective layer are independently 20-80 nm, and the thickness of the first protective layer and the second protective layer does not exceed one tenth of the thickness of the first metal layer and the second metal layer, respectively.

[0031] Preferably, the materials of the first protective layer and the second protective layer may be consistent or inconsistent, and the thicknesses may be consistent or inconsistent.

[0032] Preferably, the preparation method of the first protective layer and the second protective layer includes one or more of physical vapor deposition, chemical vapor deposition, in-situ forming, and coating.

[0033] According to a second aspect of the present invention, a battery is provided, comprising the above functional current collector. The battery prepared using the above functional current collector has good thermal stability, thus effectively improving the electrochemical performance and safety performance of the battery. DETAILED DESCRIPTION

[0034] In order to enable those skilled in the art to better understand the solutions of the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only embodiments of a part of the present invention, rather than all embodiments.

[0035] Example 1

[0036] The functional current collector of this embodiment is prepared according to the following steps:

[0037] S1. The silica particles are ultrasonically dispersed in ethanol, and the first silane coupling agent vinyl trimethoxy silane (A-171) is added thereto, and the mixture is heated to 80°C and stirred for 30 minutes, and then the reaction is stopped, cooled to room temperature, centrifuged to remove the solvent, and then dispersed in ethanol again to obtain a solution containing silane coupling agent-coated silica (modified silica); wherein the molar ratio of the silica particles to A-171 is 1:0.3;

[0038] S2. Adding a second silane coupling agent, vinyl trimethoxysilane (A-171), and the solution containing the silane coupling agent coated filler obtained in S1 to the PET polyester masterbatch, heating to 80°C for reaction for 20 minutes, and then subjecting the obtained mixture to melt-extrusion-biaxial stretching to obtain the polyester composite film having a thickness of 6 μm; wherein the molar ratio of the PET polyester masterbatch: the silane coupling agent coated filler: A-171 is 1:0.15:0.1;

[0039] S3. The polyester composite film prepared in S2 is placed in a magnetron sputtering machine, and a nickel-chromium alloy target is used as the target material to deposit a 5 nm transition layer on both sides of the polyester film. The specific process conditions are: a nickel-chromium target (purity: 99.99%) is used as the target material, the power is 4KW, the argon flow rate is 50mL / min, the coating vacuum is 0.08Pa, the coating time is 1s, and the temperature of the main roller during the coating process is 20°C;

[0040] S4. The product obtained in S3 is placed in a magnetron sputtering machine, and a copper layer (metal layer) with a thickness of 900 nm is deposited on both sides thereof. The specific process conditions are: a copper target (purity: 99.99%) is used as the target material, the power is 12.0 KW, the argon gas flow rate is 70 mL / min, the coating vacuum is 0.1 Pa, the coating time is 100 s, and the cooling temperature of the main roller during the coating process is -5°C;

[0041] S5. The product obtained in S4 is immersed in a 0.5 g / L chromic anhydride aqueous solution (25°C) for 20 seconds, and then washed with a pure water tank. After washing, it is placed in a 60°C oven for drying to prepare a functional current collector.

[0042] Example 2

[0043] The method is basically the same as Example 1, except that the first and second silane coupling agents added in S1 and S2 are both N-(2-aminoethyl)-3-aminopropyltrimethoxysilane (KH-792). The rest is the same as Example 1.

[0044] Example 3

[0045] The method is basically the same as that in Example 1, except that the first and second silane coupling agents added in S1 and S2 are both 3-aminopropyltrimethoxysilane (APTMS).

[0046] Example 4

[0047] The method is basically the same as that in Example 1, except that in S1 and S2, the first and second silane coupling agents added are both 3-mercaptopropyltrimethoxysilane (MPS). The rest is the same as that in Example 1.

[0048] Example 5

[0049] The method is basically the same as that in Example 1, except that in S1 and S2, the first and second silane coupling agents added are both bis(triethoxysilylpropyl)tetrasulfide (TESPT). The rest is the same as that in Example 1.

[0050] Example 6

[0051] The method is basically the same as that in Example 1, except that in S1 and S2, the first and second silane coupling agents added are both 3-(2,3-epoxypropoxy)propyltrimethoxysilane (KH-560). The rest is the same as that in Example 1.

[0052] Example 7

[0053] The method is basically the same as that in Example 1, except that in S1 and S2, the first and second silane coupling agents added are both 3-(methacryloyloxy)propyltrimethoxysilane (KH-570). The rest is the same as that in Example 1.

[0054] Example 8

[0055] The method is basically the same as Example 1, except that the first silane coupling agent added in S1 is N-(2-aminoethyl)-3-aminopropyltrimethoxysilane (KH-792), and the second silane coupling agent added in S2 is 3-(2,3-epoxypropyloxy)propyltrimethoxysilane (KH-560). The rest is the same as Example 1.

[0056] Example 9

[0057] The method is basically the same as that in Example 1, except that in S2, the second silane coupling agent added is 3-(methacryloyloxy)propyltrimethoxysilane (KH-570). The rest is the same as that in Example 1.

[0058] Example 10

[0059] The method is basically the same as Example 1, except that in S1, the molar ratio of silica particles to A-171 is 1:0.05. The rest is the same as Example 1.

[0060] Embodiment 11

[0061] The method is basically the same as Example 1, except that in S2, the molar ratio of PET polyester masterbatch, powder (modified silica), and A-171 is 1:0.1:0.1. The rest is the same as Example 1.

[0062] Example 12

[0063] The method is basically the same as Example 1, except that in S2, the molar ratio of PET polyester masterbatch, powder (modified silica), and A-171 is 1:0.2:0.1. The rest is the same as Example 1.

[0064] Example 13

[0065] The method is basically the same as Example 1, except that in S2, the molar ratio of PET polyester masterbatch, powder (modified silica), and A-171 is 1:0.25:0.1. The rest is the same as Example 1.

[0066] Embodiment 14

[0067] The method is basically the same as Example 1, except that in S2, the molar ratio of PET polyester masterbatch, powder (modified silica), and A-171 is 1:0.3:0.1. The rest is the same as Example 1.

[0068] Embodiment 15

[0069] The method is basically the same as that in Example 2, except that: in S1, epoxy resin is used as filler, and the molar ratio of epoxy resin to KH-792 is also 1:0.3. The rest is the same as that in Example 2.

[0070] Example 16

[0071] The method is basically the same as Example 16, except that in S1 and S2, the added silane coupling agent is APTMS. The rest is the same as Example 15.

[0072] Embodiment 17

[0073] The method is basically the same as that of Example 15, except that the silane coupling agent added in S1 and S2 is KH-560. The rest is the same as that of Example 15.

[0074] Embodiment 18

[0075] The method is basically the same as that in Example 1, except that the second silane coupling agent vinyltrimethoxysilane (A-171) is not added to S2. The rest is the same as that in Example 1.

[0076] Comparative Example 1

[0077] The method is basically the same as Example 1, except that no modified silica filler is added, and the specific measure is that a 6 μm polyester film is prepared using a polyester masterbatch with a content of 100%. The rest is the same as Example 1.

[0078] Comparative Example 2

[0079] It is basically the same as Example 1, except that: the specific operation in S1 is as follows: the silica particles are ultrasonically dispersed in ethanol to obtain an unmodified silica solution; the specific operation in S2 is as follows: the PET polyester masterbatch and the unmodified silica solution are mixed, wherein the molar ratio of the PET polyester masterbatch: the unmodified silica is 1:0.15, and then the obtained mixture is melt-extruded-biaxially stretched to obtain a polyester composite film with a thickness of 6 μm; the rest is the same as Example 1.

[0080] Test Case

[0081] 1. Experimental Construction Method

[0082] Here, the high temperature cycle performance and safety performance of the battery assembled with the functional current collectors prepared in the above embodiments and comparative examples are tested. The specific test method is as follows:

[0083] Battery Assembly:

[0084] For the positive electrode, the positive electrode current collector is made of aluminum foil (thickness is 13 μm), and the positive electrode material is LiNi 0.6 Mn 0.2 Co 0.2 O2(NCM622);

[0085] For the negative electrode: the negative electrode current collector adopts the functional current collector prepared in the above embodiment and comparative example, and the negative electrode material adopts artificial graphite;

[0086] For the diaphragm, alumina ceramic coated polyethylene diaphragm (thickness 25 μm) was used;

[0087] For the electrolyte, 1 mol·L -1 The carbonate solution of LiPF6, the solvent is a mixture of propylene carbonate, ethylene carbonate and ethyl methyl carbonate, and the molar ratio of the three is 1:1:1;

[0088] The above materials are used to assemble a lithium-ion battery.

[0089] (1) High temperature cycle performance test:

[0090] The test steps include: 1) at 45°C, discharge the battery cell with a current of I1 (1 hour discharge current) to the discharge termination voltage, and let it stand for 30 minutes; 2) charge the battery cell with a constant current of I1 to the charge termination voltage, then switch to constant voltage charging, and stop charging when the charge termination current drops to 0.05 times of I1, and let it stand for 30 minutes after charging; 3) discharge the battery cell with a current of I1 to the discharge termination voltage; 4) cycle continuously for 500 times according to steps 1)-3), record the battery capacity at the first cycle and the 500th cycle, and calculate the battery capacity retention rate, which is the battery capacity at the 500th cycle / the battery capacity at the first cycle × 100%.

[0091] (2) Safety performance test:

[0092] The safety performance of the battery is verified by a needle puncture test, as follows: the battery prepared above is placed in a needle puncture test device, wherein the diameter of the needle is 3mm, the puncture speed is 10mm / s, the sampling interval is 100ms, and the sampling time is 15min. If the safety performance is qualified, the battery should not explode, catch fire, or smoke. 100 batteries are used as test samples, and the safety performance = (number of batteries with qualified safety performance / 100) × 100%.

[0093] 2. Experimental results

[0094] The high temperature cycle performance of the functional current collectors prepared in the above embodiments and comparative examples and the safety performance test results of the assembled batteries are shown in Table 1.

[0095] Table 1 High temperature cycle performance of functional current collectors prepared in the examples and comparative examples and safety performance test results of their assembled batteries

[0096]

[0097]

[0098] It can be seen from Table 1 that the functional current collector provided by the present invention can effectively improve the thermal stability and anti-swelling and dissolution properties of the polyester composite film, thereby effectively improving the electrochemical properties (such as high-temperature cycle performance) and safety performance of the battery prepared with the functional current collector, with specific reference to the data of Examples 1 to 18.

[0099] In Comparative Example 1, no modified silica filler was added, and in Comparative Example 2, unmodified silica was added, which resulted in a decrease in the high-temperature cycle performance and safety performance of the battery. This shows that not adding modified silica filler or only adding unmodified silica cannot effectively improve the thermal stability and anti-swelling and dissolution performance of the polyester composite film, and therefore cannot effectively improve the high-temperature cycle performance and safety performance of the battery prepared with the same.

[0100] Further observation of Examples 1 to 9 shows that adding different silane coupling agents to modify silica particles and polyester films can make the battery have better high-temperature cycle performance and safety performance, which shows that adding different silane coupling agents to modify silica particles and polyester films can effectively improve the thermal stability and anti-swelling and dissolution performance of the polyester composite film, and further improve the high-temperature cycle performance and safety performance of the battery prepared therefrom. In Examples 8 and 9, the types of silane coupling agents added to S1 and S2 are different, and the performance of the battery in Example 8 is better, which shows that the suitable silane coupling agent combination in S1 and S2 has a better modification effect on the polyester composite film, and is therefore more conducive to further optimizing the high-temperature cycle performance and safety performance of the battery.

[0101] Comparing Example 1 and Example 10, the amount of the first silane coupling agent added in Example 10 is too small, which also causes the relevant performance of the battery to decrease. This shows that controlling the amount of the first silane coupling agent (or the second silane coupling agent) within a specific range is more conducive to the comprehensive modification of the polyester film composite film, improving the comprehensive performance of the polyester composite film, and further optimizing the relevant performance of the battery.

[0102] Comparing Example 1 with Examples 11 to 14, the amount of modified silicon dioxide added in Example 14 is too high, which is not conducive to further improving the high-temperature cycle performance and safety performance of the battery. This shows that it is necessary to ensure that the added modified silicon dioxide is within a specific range in order to improve the overall performance of the polyester composite film and achieve the purpose of further optimizing the battery performance.

[0103] By observing Examples 15 to 17, it can be seen that when silicon dioxide is adjusted to epoxy resin, a polyester composite film with good performance can also be obtained, so the prepared battery also has good high-temperature cycle performance and safety performance.

[0104] Comparing Example 1 and Example 18, in Example 18, no second silane coupling agent is added to S2, which makes the modification effect on the polyester composite film worse, resulting in a decrease in the high-temperature cycle performance and safety performance of the battery.

[0105] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the protection scope of the present invention. Although the present invention is described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the technical solutions of the present invention can be modified or equivalently replaced, but these modifications or replacements are all within the protection scope of the present invention.

Claims

1. A functional current collector, characterized in that: It includes a base film, wherein the base film is a polyester composite film; The polyester composite film comprises polyester and filler, and the filler is coated by a first silane coupling agent; The filler is an inorganic material or a polymer; The general structural formula of the first silane coupling agent is (R1O)3-Si-R2-R3; Wherein, R1 includes: substituted or unsubstituted C1-C4 alkyl; R2 includes one of the following: substituted or unsubstituted C1-C18 straight-chain alkyl, substituted or unsubstituted C1-C18 branched alkyl, substituted or unsubstituted C2-C18 straight-chain alkenyl with at least one double bond, substituted or unsubstituted C2-C18 branched alkenyl with at least one double bond, substituted or unsubstituted C2-C18 straight-chain alkynyl with at least one triple bond, substituted or unsubstituted C2-C18 branched alkynyl with at least one triple bond, substituted or unsubstituted C3-C18 saturated cycloalkyl, substituted or unsubstituted C3-C18 at least partially unsaturated cycloalkyl, substituted or unsubstituted C3-C18 saturated cycloalkyl without -NH-, substituted or unsubstituted C3-C18 saturated cycloalkyl and containing at least one -NH-; R3 includes one of the following: hydroxyl, amino, vinyl, mercapto, acrylate, epoxy, halogen, and alkali metal groups.

2. The functional current collector according to claim 1, characterized in that: R3 includes one of the following: vinyl, amino, mercapto, epoxy, acrylate.

3. The functional fluid collector according to claim 1, characterized in that: The polyester composite film has a thickness of 1.0-10 μm.

4. The functional fluid collector according to claim 1, characterized in that: The inorganic material includes at least one of carbon black, graphite, graphene, aluminum, zinc, aluminum oxide, zinc oxide, iron oxide, silicon dioxide, titanium dioxide, montmorillonite, kaolin, calcium carbonate, and glass fiber; The polymer includes at least one of polyamide resin, epoxy resin, phenolic resin, polycarbonate resin, polyamide resin, and acrylonitrile-butadiene-styrene copolymer resin.

5. The functional current collector according to claim 1, characterized in that: The preparation of the polyester composite film comprises the following steps: S1. dispersing the filler in a first alcohol solvent, adding the first silane coupling agent thereto, wherein the molar ratio of the filler to the first silane coupling agent is 1:(0.1-0.5), heating to 75-85° C. for reaction for 20-50 min, cooling, centrifuging to remove the solvent, and dispersing again in a second alcohol solvent to obtain a solution containing the first silane coupling agent-coated filler; S2. Add a second silane coupling agent and the solution containing the first silane coupling agent coated filler obtained in S1 to the polyester masterbatch, heat to 75-85°C and react for 10-30 minutes, and then obtain the polyester composite film by melt-extrusion-biaxial stretching of the obtained mixture; wherein the molar ratio of the polyester masterbatch: the first silane coupling agent coated filler: the second silane coupling agent is 1:(0.1-0.25):(0.01-0.2).

6. The functional fluid collector according to claim 5, characterized in that: The first silane coupling agent and the second silane coupling agent are of the same type; Or, the first silane coupling agent and the second silane coupling agent are of different types.

7. The functional fluid collector according to any one of claims 1 to 6, characterized in that: It comprises in sequence a first protective layer, a first metal layer, a first transition layer, the polyester composite film, a second transition layer, a second metal layer and a second protective layer.

8. The functional fluid collector according to claim 7, characterized in that: The first transition layer and the second transition layer independently include at least one of aluminum oxide, silicon oxide, titanium oxide, nickel, chromium, titanium, nickel-chromium alloy, nickel-chromium-copper alloy, and silicon-aluminum alloy; The first metal layer and the second metal layer independently include at least one of aluminum, copper, gold, silver, nickel, zinc, or a metal alloy formed by a combination of at least two of the above metals; The first protective layer and the second protective layer independently include at least one of nickel, chromium, nickel-chromium alloy, nickel-based alloy, copper-based alloy, copper oxide, aluminum oxide, nickel oxide, chromium oxide, cobalt oxide, copper-chromium oxide, graphite, carbon black, carbon nano-quantum dots, carbon nanotubes, carbon nanofibers, graphene and graphene oxide.

9. The functional fluid collector according to claim 8, characterized in that: The thickness of the first transition layer and the second transition layer are independently 5-50 nm; The thickness of the first metal layer and the second metal layer are independently 400-2000 nm; preferably, the thickness of the first metal layer and the second metal layer are independently 800-1200 nm; The thickness of the first protective layer and the second protective layer are independently 10-100 nm.

10. A battery, characterized in that: Comprising the functional current collector as described in any one of claims 1-9.

Citation Information

Patent Citations

  • Silicon-base negative material with silane coupling agent and conductive polymer two-layer cladding structure as well as preparation method and application of material

    CN103996834A

  • Battery electrode, preparation method thereof, and all-solid-state battery

    CN109216701A

  • Functional current collector for adsorbing heavy metal ions and preparation method thereof

    CN117334922A

  • Composite current collector and preparation method and application thereof

    CN118263449A

  • Composite current collector and preparation method and application thereof

    CN118522901A